Factors Influencing Interpersonal Communication Among Fieldwork Students in the Hospitality Industry in Central Java - Susmono Widagdo, Chrisostomus; Supriyanto, Sapto; Hadi, Syamsul; Abdul Jabbar, Umar; Intiar, Septa (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Study This digs into factors influencing the interpersonal communication of students studying in the hotel industry. Students face various challenges in communicating with colleagues, guests, and superiors in an environment often full of diverse cultures And demands Work tall. Studies This identifies several factors that play a role key in the interpersonal interactions of students, including different cultures, lack of experience in Work, skills, poor communication, level of stress And pressure work, role, And not quite enough answers that are not clear, ability to settle the conflict, and awareness of self. Study This demonstrates the need for a deep understanding of factors. This helps students overcome constraints in interpersonal communication. Results study. This can give educators an outlook and institutional training. For designing a suitable program, use increased skills in interpersonal communication for students studying the hotel industry field. With a better understanding of the factors that influence interpersonal communication, the expected students can build effective relationships in the environment, improve their trust in themselves, contribute positively to the hotel industry, and develop their careers in the past.